2014
DOI: 10.1590/1678-775720140067
|View full text |Cite
|
Sign up to set email alerts
|

Influence of periodontal ligament simulation on bond strength and fracture resistance of roots restored with fiber posts

Abstract: ObjectiveConsidering that periodontal ligament simulation may influence the stress distribution over teeth restored with intraradicular retainers, this study aimed to assess the combined effect of mechanical cycling and periodontal ligament simulation on both the bond strength between fiber posts and root dentin and the fracture resistance of teeth restored using glass fiber posts.Material and MethodsNinety roots were randomly distributed into 3 groups (n=10) (C-MC: control; P-MC: polyether; AS-MC: addition si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 25 publications
(60 reference statements)
1
35
0
1
Order By: Relevance
“…Although Marchionatti et al 33) stated that no differences were found between the groups with and without periodontal ligament for the fracture resistance of roots treated with fiber post, Soares et al 51) reported that periodontal ligament affected the fracture resistance and fracture modes by behaving as a stress absorber. The authors of this study preferred to use periodontal ligament simulation prior to the fracture strength analysis of endocrowns, in order to better simulate the real tooth behavior against masticatory forces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Marchionatti et al 33) stated that no differences were found between the groups with and without periodontal ligament for the fracture resistance of roots treated with fiber post, Soares et al 51) reported that periodontal ligament affected the fracture resistance and fracture modes by behaving as a stress absorber. The authors of this study preferred to use periodontal ligament simulation prior to the fracture strength analysis of endocrowns, in order to better simulate the real tooth behavior against masticatory forces.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas periodontal ligament simulation was used in some literatures 33,50) , there are studies which reported that periodontal ligament is challenging in terms of thickness standardization and stability 14,35,37) . Although Marchionatti et al 33) stated that no differences were found between the groups with and without periodontal ligament for the fracture resistance of roots treated with fiber post, Soares et al 51) reported that periodontal ligament affected the fracture resistance and fracture modes by behaving as a stress absorber.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All teeth were mounted in epoxy resin (IN2 INFUSION; Easy Composites, USA) blocks using a plastic ring (25 × 35 mm). To simulate the function of the periodontium, the root was covered with thin layer of condensation silicone (Zetaplus; Zhermack-SpA, Italy) 10 . A specially designed centralizing device was fabricated to allow accurate centralization of the tooth in the plastic ring during construction of the epoxy resin block ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Crosshead speeds vary from 0.01 mm/min to 10 mm/min and various studies were performed to study the influence of test speed on the bond strength tests [70,75,85,98,135,145,146,[161][162][163][164][165][166][167][168]172]. Unlike controversial results of the macro-tests, when measuring micro-tensile bond strengths, some studies have reported that the influence of crosshead speed is insignificant [167,168].…”
Section: Crosshead Speedsmentioning
confidence: 99%